Green synthesis of biodiesel from Citrus medica seed oil using green nanoparticles of copper oxide - Rozina; Chia S.R.; Ahmad M.; Sultana S.; Zafar M.; Asif S.; Bokhari A.; Nomanbhay S.; Mubashir M.; Khoo K.S.; Show P.L. (Elsevier Ltd, 2023)
Catalysts; Copper oxides; Energy policy; Esters; Feedstocks; Fourier transform infrared spectroscopy; Gas chromatography; Mass spectrometry; Nanoparticles; Nuclear magnetic resonance spectroscopy; Oils and fats; Renewable energy resources; Scanning electron microscopy; Synthesis (chemical); Synthetic fuels; Transesterification; Biodiesel production; Citrus medica; Copper oxide catalysts; Edible seed oil; Green nanoparticle; Green synthesis; Methyl esters; Non-edible seed oil; Seed oil; Synthesised; Biodiesel